Voltage THD Analysis on the Use of DC Motors in Steel Milling Process - Muzakki, Rizdam Firly; Irianto, Chairul Gagarin (DPTE FT UNY, 2023)
A milling process utilize DC motors and rectifier circuits. Semiconductor components in the rectifier circuit could cause harmonic distortion. At PT X, the voltage THD generated at the 6KV feeder panel has exceeded the standards set by the IEEE. This study aims to analyze the voltage THD caused by a controlled rectifier circuit and DC motors, and to design a filter to mitigate it. MATLAB software is used to analyze the THD voltage. From the simulation results, it is known that the 400KW, 450KW, and 600KW DC motors produce voltage THD values of 9.35%, 14.23%, and 12.28% respectively which exceed the set standards of 8%. A single-tuned passive filter is designed to reduce the THD voltage value on each motor. The installation of the filter effectively reduces the THD voltage value in the 400KW, 450KW, and 600KW DC motors to 4.34%, 5.38%, and 6.35% respectively.